2014
DOI: 10.2174/1876817201406010009
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic and Predicting Roles of Tumor-Infiltrating Lymphocytes in Breast Cancer: A Meta-Analysis

Abstract: Background:The relationship between lymphocyte infiltrates (LIs) and breast cancer outcome remains controversial. We performed this meta-analysis to elucidate the relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Nonetheless, TNBCs and HER2+ BCs grow despite high CTL infiltration, a finding suggesting that their mere presence is not reflecting effective immune function. In the clinical outcome analysis, high CD8+ TILs were associated with significantly prolonged BCSS, DFS and DMFS either in the entire group or the HR-subgroup, but not in the HR+ patients, in accordance to published reports (25,34,43,51,55,56,59,65). Total CD8+ TILs, namely intraepithelial and stromal TILs, are also shown as a prognostic factor for better OS, DFS and BCSS, especially in TNBC (66,67).…”
Section: Discussionsupporting
confidence: 86%
“…Nonetheless, TNBCs and HER2+ BCs grow despite high CTL infiltration, a finding suggesting that their mere presence is not reflecting effective immune function. In the clinical outcome analysis, high CD8+ TILs were associated with significantly prolonged BCSS, DFS and DMFS either in the entire group or the HR-subgroup, but not in the HR+ patients, in accordance to published reports (25,34,43,51,55,56,59,65). Total CD8+ TILs, namely intraepithelial and stromal TILs, are also shown as a prognostic factor for better OS, DFS and BCSS, especially in TNBC (66,67).…”
Section: Discussionsupporting
confidence: 86%
“…Previous VTA studies analyzing the prognostic impact of stromal TILs across various cutoff points on TNBC have yielded promising results [3][4][5][6]8]. A meta-analysis by Ibrahim et al [42] also revealed that every 10% increment in TILs might lead to a 15À20% reduction in disease recurrence or mortality in TNBC patients. On the other hand, a cutoff point of 10% for the TIL fraction, which was used in the CTA algorithm developed by Amgad et al [39], did not have any significant impact on overall survival in the breast cancer subgroup.…”
Section: Cohortmentioning
confidence: 99%
“…However, the picture of how tumor‐invasive immune cells and receptor subtypes are related in breast cancer remains incomplete. Reviews summarizing the association of TIL infiltration with survival in breast tumors show that outcomes depend on how immune cells are measured, which cell types are included, and how they modify the pathogenesis in different subtypes 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…Reviews summarizing the association of TIL infiltration with survival in breast tumors show that outcomes depend on how immune cells are measured, which cell types are included, and how they modify the pathogenesis in different subtypes. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%